2016
DOI: 10.15740/has/ijfci/7.1/7-13
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of different tree species for carbon sequestration under wasteland condition

Abstract: A study was conducted to identify suitable fast growing trees under wasteland condition for carbon sequestration. Accordingly, five fast growing trees namely Tectona grandis Linn. , Gmelina arborea Roxb., Dalbergia sissoo Roxb., Bambusa vulgaris var. vulgaris and Swietenia macrophylla king were selected for field study under wasteland condition. The performance of these trees was assessed with biometrical traits (height, basal diameter) and eco-physiological traits (transpiration, photosynthesis, intercellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…andBheemaiah et al (1997) reported that maximum height increment in Casuarina may be attributed to micro irrigation with regular intervals. In supporting the present result,Balasubramanian et al (2017); HariPrasath et al (2016a), and Kandell…”
supporting
confidence: 88%
“…andBheemaiah et al (1997) reported that maximum height increment in Casuarina may be attributed to micro irrigation with regular intervals. In supporting the present result,Balasubramanian et al (2017); HariPrasath et al (2016a), and Kandell…”
supporting
confidence: 88%
“…Throughout the globe, the term waste is associated with "bare" [10] and "improper" for economic utility [43], as well as untamed [44] and "standing apart" from human utilization due to regional constraints. However, in certain regions of the Global South, particularly in Southeast Asian countries, the escalating rate of population growth and increasing human demands necessitate higher food production, thereby requiring more extensive land utilization [24,37]. The term waste keeps oscillating over time concerning the physical and geopolitical set up of a region and based on that, we seek to explain the wasteland concept separately in the Global North and South for a better understanding.…”
Section: Understanding the Concept Of Wasteland In Global Contextmentioning
confidence: 99%
“…This makes wasteland a common property resource [77]. The reasons for untapped rural wastelands in the Global South are diverse, where there is over-dependency on current cropland [24], a lack of comprehensive land-use policy [37] and economic constraints [44], which are recognized as the leading factors. However, to achieve effective land utilization in order to respond to needs arising from the increasing population growth rate, some countries in the Global South have implemented effective wasteland reclamation policies to convert unused land into an economic good (Table A1 Appendix A).…”
Section: Understanding the Concept Of Wasteland In Global Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, about 69 million hectares (ha) of land in India are considered waste in areas defined as rural areas. Out of which, about 50% of lands are categorized as non-forest lands that can be converted into fertile land [37]. Converting wasteland into farmland may protect current fertile cropland from degradation [38], can full fill the demand for food, reduce poverty, and restore the ecology at the national level [39].…”
Section: Introductionmentioning
confidence: 99%